Environmental indicators in a sustainable mining - Díaz Lazo, Joel H. (2019)
Mining industry in Peru has a lot of regulatory requirements, even more than any other industry, that is why it is necessary to manage all the possible negative environmental impacts that can occur in the mining area of influence, both indirect and direct. Mining industry must be able to quantify, qualify and interpret its sustainability performance, and simultaneously, it must demonstrate its continuous improvements in the short and long term. This study aims to apply environmental indicators in the Environmental Management System of Atacocha Mining Unit (currently Nexa Mining Unit), which has been established as the study area. This would allow the researchers to have an overview, although limited, of the performance of its Environmental Management System. According to the results obtained, we could conclude that the use of Environmental Management Indicators contributes in the assessment of the environmental management and quality in sustainable mining projects. With these tools, we could take the project towards a new paradigm of sustainable development